Anosognosia of financial ability in mild cognitive impairment. (3rd May 2019) - Gerstenecker, Adam; Martin, Roy C.; Triebel, Kristen L.; Marson, Daniel C.
Abstract : Objectives: Although financial ability has been well‐studied in mild cognitive impairment (MCI) and Alzheimer's disease (AD) using performance‐based financial capacity assessment instruments, research is limited investigating everyday financial problems and declines in persons with AD and MCI and the insight of people with MCI to recognize that financial capacity declines are occurring. To address this gap in the research, we investigated everyday financial activities and skills in a sample of older adults representing the dementia spectrum. Methods: Participants were 186 older adults in three diagnostic classifications: cognitively healthy, MCI likely due to AD, and mild AD dementia. Everyday financial ability was assessed using the Current Financial Activities Report (CFAR). The CFAR is a standardized report‐based measure which elicits participant and study partner ratings about a participant's everyday financial abilities. Results: Results showed that both CFAR self‐ and study partner‐report distinguished diagnostic groups on key financial capacity variables in a pattern consistent with level of clinical pathology. Study partner‐report indicated higher levels of financial skill difficulties in study participants than did the self‐report of the same study participants. Study partner‐ratings were more highly correlated with participant scores on a performance‐based measure of financial capacity than were participant self‐ratings. Results also showed that loss of awareness of financial decline is emerging at the MCI stage of AD. Conclusions: People with MCI represent a group of older adults at particular risk for financial missteps and—similar to people with AD—are in need of supervision of their financial skills and activities.